Long-Term Outcomes for Chinese COPD Patients After PCI: A Propensity Score Matched, Double-Cohort Study - Zheng, Yitian; Qi, Yu; Seery, Samuel; Wang, Wenyao; Zhao, Wei; Shen, Tao; Zhou, Lequn; Yang, Jie; Li, Chen; Wang, Xuliang; Gao, Jun; Meng, Xiangbin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives The aim of this study was to analyze long-term outcomes of Chinese coronary artery disease (CAD) patients with (and without) chronic obstructive pulmonary disease (COPD) after percutaneous coronary intervention (PCI). Background Chronic obstructive pulmonary disease is a chronic condition which often develops in conjunction with CAD. PCI is a core therapy for CAD, although we still need to understand CAD-COPD outcomes and to identify factors that influence prognoses, across ethnicities. Methods This double-cohort study involved 12,343 Chinese CAD patients who received PCI. Baseline characteristics were collected in two independent, specialty centers. Propensity-score matching was performed to control confounding factors, using a nearest neighbor matching method within a 0.02 caliper and on a propensity score scale of 0.1 for each center. Comorbid CAD-COPD cases were compared to non-COPD patients in terms of major adverse cardiac events (MACEs). Results Patients with COPD were generally older than those without COPD (65.4 ± 9.2 vs. 58.2 ± 10.3, p < 0.001). There were no significant differences in the end points between COPD and non-COPD groups after PCI (All p > 0.05); however, the incidence of MACEs increased after 450 days. Further subgroup analysis suggests that COPD is approximately four times more prevalent among those aged over 75 years (HR, 3.818; 95%CI, 1.10–13.29; p = 0.027) and those aged below 55 years (HR = 4.254; 95% CI, 1.55–11.72; p = 0.003). Conclusion Having COPD does not appear to have a significant impact on CAD outcomes 2 years after PCI, and beyond. However, an increasing number of MACEs was observed after 450 days, which suggests that there may be a double-stage effect of COPD on PCI prognosis. There is a need for focused comorbidity management, specifically for those aged below 55 years and above 75 years.